Climate Change and Arboviral Diseases: Challenges for Surveillance and Primary Health Care - Maria Terezinha Gomes Pontes; Edylene Maria dos Santos Pereira; Bruno Ramos Brum; Maria Aparecida de Almeida Araujo; Thaita Thaisi Zago; Sérgio Raimundo Ernesto Machado; Sheila Érika Ferro Ramalho Nobre; Neide Moreira de Souza (RSV, 2026)
Climate change has emerged as one of the greatest public health challenges of the twenty-first century, profoundly influencing the epidemiology of infectious diseases worldwide. Among the health conditions most directly affected by environmental transformations are arboviral diseases, including dengue, Zika, chikungunya, and yellow fever, whose transmission dynamics are highly sensitive to variations in temperature, rainfall, humidity, urbanization, and ecosystem disruption. These climatic and environmental changes have expanded the geographic distribution of mosquito vectors, prolonged transmission seasons, and increased the frequency and intensity of outbreaks in tropical and subtropical regions. In countries such as Brazil, where arboviruses already represent a significant public health burden, climate change has intensified existing vulnerabilities and imposed new demands on health systems, particularly regarding disease surveillance, prevention, and healthcare delivery. This academic essay critically examines the relationship between climate change and the growing burden of arboviral diseases, emphasizing the challenges faced by epidemiological surveillance systems and Primary Health Care (PHC). The discussion explores the ecological mechanisms linking climate variability to vector proliferation, the organizational implications for health services, the importance of integrated surveillance, and the strategic role of PHC in prevention, early diagnosis, community engagement, and intersectoral action. The essay argues that strengthening climate-sensitive health governance and resilient primary healthcare systems is essential for reducing the health impacts of climate-driven arboviral transmission and protecting vulnerable populations.